2013
DOI: 10.1016/j.drugalcdep.2013.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers in treatment seeking for cannabis dependence

Abstract: Facilitators and barriers in treatment seeking for cannabis dependence van der Pol, P.; Liebregts, N.; de Graaf, R.; Korf, D.J.; van den Brink, W.; van Laar, M. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 30 publications
2
53
0
Order By: Relevance
“…One may argue that this marks their increased risk for the following relapse. The importance of functional impairment is underlined by our recent finding that functional impairment was the strongest reason to seek treatment for patients in addiction care, while in the current sample, one of the main self-reported barriers to seek treatment was thinking that treatment was not needed [15], in line with a previous study among frequent cannabis users [56]. This may also explain the low treatment seeking rates between T0 and T2.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…One may argue that this marks their increased risk for the following relapse. The importance of functional impairment is underlined by our recent finding that functional impairment was the strongest reason to seek treatment for patients in addiction care, while in the current sample, one of the main self-reported barriers to seek treatment was thinking that treatment was not needed [15], in line with a previous study among frequent cannabis users [56]. This may also explain the low treatment seeking rates between T0 and T2.…”
Section: Discussionsupporting
confidence: 72%
“…Currently, levels of cannabis use or related problems following a period of cannabis dependence have only been quantified among remitted patients from clinical samples [9,13,14] and results are thus influenced by the treatment itself and the selection of more severe cases typically seen in treatment [15,16]. It is therefore important to know more about cannabis use, cannabis use problems and functional impairment of cannabis-dependent individuals in the community who remit from dependence compared to persistent dependent users.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of self-efficacy to resist cannabis when experiencing distress may motivate individuals to seek help because they believe they are unable to make effective changes on their own. Past research has shown that treatment seekers are likely to have had more prior quit attempts than nontreatment seekers (van der Pol et al, 2013). Treatment seekers' self-efficacy may therefore have been reduced as a result of failed past attempts (Bandura, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have found several characteristics that differ between these groups. Treatment seekers are more likely to have comorbid mental health problems, experience greater impairment as a result of their cannabis use, and encounter more problems (e.g., withdrawal symptoms) when attempting to quit cannabis (Agosti and Levin, 2009;Pacek and Vandrey, 2014;van der Pol et al, 2013). They also differ in motivation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation